Inovação e ciclos econômicos em Schumpeter e Minsky - Araujo, Joelma Maria Batista de (2012)
The current global economic crisis has put into question the elucidating ability of many economic approaches, in particular those based on neoclassical assumptions, marked roughly by the tendency to equilibrium (self-tuning) as well as the treatment of superficial functions of money in the capitalist system. Similarly, the work of some authors from the heterodox line has gained more space in discussions precisely because give special attention to the role of money in the functioning of the capitalist economic dynamics, and also observe the system on the prism of inherent instability. Regarding the crisis, the mainstream has pointed to possible failures of economic policies of the U.S. government, in turn, heterodox analyzes have indicated, generally, the lack of regulation of financial markets. Beyond these interpretations, however, one of the most striking elements of this process - from the formation of the bubble subprime crisis - were financial innovations that led to the emergence of a period of global economic prosperity. Thus it broadens the perception of innovation as an important element in the formation of economic cycles, encouraging discussion and research on both topics. In order to further explore the relationship between theories that treat innovation as a key driver of the business cycle, we propose an analysis of rapprochement between the views of business cycles from Schumpeter and Minsky. The differences between the heuristic models used in their analysis are considerable, but it is precisely here that lies the challenge and the goal of this dissertation: trying to establish a complementarity between the views of cycle from the two economists, despite the differences in their models. Thus, the hypothesis holds that innovation is central in explaining business cycles in the theoretical approaches of Schumpeter and Minsky, which makes their visions of the dynamics of a market economy complementary. There is, therefore, the question: Is it possible to explain the centrality that has innovations in explaining business cycles from the complementarity of the views of Schumpeter and Minsky cycle? In making this dissertation it was applied the methodology of assessment literature. We exposed the differences between the theories of the business cycle of Minsky and Schumpeter, but also identified traits in common in the views of the two. Above all, despite the differences between the theoretical legacies and heuristic models, it was observed that the visions of cycle from the two economists have considerable approaches together. It was observed that, in fact, the views of Schumpeter and Minsky cycles are complementary. According to Vercelli assumption there is a relation of complementarity among the cycles of the two economists. However, the main question of this dissertation concerns the complementary of cycle visions from Schumpeter and Minsky. However, it is not entirely abandoned the Vercelli assumption since, based on what has been discussed, it can be stated that financial innovations possibly arising on market conditions similar to that tend to arise technological innovations (relative stability, for example). Although, not necessarily, the two cycles has to occur simultaneously and dependent. In short, we can say that a reconciliation between the vision of technological cycle of Schumpeter and vision of Minsky's financial cycle is able to make more explicit the cyclical dynamics of the capitalist system and the role of innovation in this process. Thus we conclude that innovation is central in explaining business cycles in the theoretical approaches of Schumpeter and Minsky, which makes their visions of the dynamics of a market economy complementary.